Anatomical variations of the cecum and vermiform appendix: Basis for a new nomenclature for McBurney’s points - Kabanga, Thomas K.; KILARA KAPENE, Tarcisse; Kapinga, Blaise M.; Kazadi, Deogratias B.; Kabanga, Alice T.; Kabanga , Herve K.; Kabongo, Jeamarie M. (Orapuh Journal, 2025)
Introduction Appendicitis is one of the most common surgical emergencies worldwide, resulting from inflammation of the vermiform appendix attached to the cecum. Although pain is classically localised at McBurney’s point, the lack of consensus regarding its precise position, as highlighted by the studies of Karim and Naraysing, continues to fuel diagnostic and surgical debate. These uncertainties emphasise the need for a clearer understanding of the anatomical variations of the cecum and appendix to improve clinical accuracy and surgical outcomes. Purpose To describe and analyse anatomical variations of the cecum and vermiform appendix in order to assess their topographical and clinical implications. It is hypothesised that these variations influence the location of McBurney’s point and may affect diagnostic accuracy and surgical planning. The study also aims to propose a standardised anatomical nomenclature for McBurney’s point, which could enhance its clinical and surgical relevance. Methods A prospective descriptive study on the vermiform appendix was conducted between January 2017 and December 2022 in three hospitals in Kinshasa. The sample comprised 160 patients, selected by non-probability convenience sampling, who underwent midline infra-umbilical laparotomy. Intraoperative observations were collected, entered into Excel, and analysed using SPSS v20.0. Proportions were compared using the chi-square test, with statistical significance set at p < 0.05. Results In the study population (n = 160), females predominated (115; 71.9%, sex ratio = 2.56), and younger subjects were overrepresented, with the 11–20-year age group being the most frequent (60; 37.5%). The iliac position of the cecum was the most common (95; 59.4%), and a mobile cecum was observed in 124 cases (77.7%). The appendiceal base corresponded to the midpoint of McBurney’s line in 52 patients (32.5%). The appendix was mainly cylindrical (129; 80.6%), with a length between 7 and 12 cm in 86 patients (53.8%). The iliac position of the cecum predominated among patients aged 3–22 years (57; 35.6%), with a statistically significant difference (p = 0.023). Conclusion The study confirms the anatomical variability of the cecum and appendix. The cecum was predominantly mobile in the right iliac fossa, and the appendix, cylindrical and of medium length, often adopted a descending position. The appendicular base projected mainly on the umbilical–spinal line, justifying the use of the terms mid umbilical–spinal point and lateral umbilical–spinal point. These findings support promoting the laparoscopic approach to improve appendicitis management and reduce complications associated with anatomical variations.